2008
DOI: 10.1093/pasj/60.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

The 2006 November Outburst of EG Aquarii: the SU UMa Nature Revealed

Abstract: We report on time-resolved CCD photometry of the cataclysmic variable EG Aquarii during a 2006 November outburst. During the outburst, superhumps were unambiguously detected with a mean period of 0.078828(6) d, allowing for the first time to classify the object as an SU UMa-type dwarf nova. It also turned out that the outburst contained a precursor. At the end of the precursor, immature profiles of humps were observed. By a phase analysis of these humps, we interpreted the features as being superhumps. This is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…CSS 2325−08, or CSS 080101:232519−081819, is one of the first CVs to be found in the CSS survey and was a rediscovery of the known dwarf nova EG Aqr. Imada et al (2008) observed a superoutburst in EG Aqr in 2006 November and found a superhump period of 113.51 min. We observed EG Aqr at a quiescence brightness of r ∼ 19.3 in 2008 October; the details are given in Table 1 and the light curves in Fig.…”
Section: Eg Aqr (Css 080101:232519−081819)mentioning
confidence: 98%
“…CSS 2325−08, or CSS 080101:232519−081819, is one of the first CVs to be found in the CSS survey and was a rediscovery of the known dwarf nova EG Aqr. Imada et al (2008) observed a superoutburst in EG Aqr in 2006 November and found a superhump period of 113.51 min. We observed EG Aqr at a quiescence brightness of r ∼ 19.3 in 2008 October; the details are given in Table 1 and the light curves in Fig.…”
Section: Eg Aqr (Css 080101:232519−081819)mentioning
confidence: 98%
“…For example, stage-A was absent during the 2005 superoutburst of V391 Cam (Imada et al, 2009), despite the fact that the observations started from the onset of the superoutburst. Another example is the 2006 superoutburst of EG Aqr which showed a decrease of the superhump period during stage-B (Imada et al, 2008). Our statistical study suggests that systems with a superhump period longer than 0.08 days tend to show negative period derivatives during stage-B.…”
Section: Textbook Of Superhump Period Changementioning
confidence: 66%